Growth Performance and Nutritional Analysis of Spirulina platensis in Different Concentrations of Papaya Skin Powder Media (Bangladesh Journal of Scientific and Industrial Research, 2011)
The growth performance of Spirulina platensis was studied in four different concentrations viz. 0.3, 0.4, 0.5 and 0.6 g/l of papaya (Carica papaya) skin powder media (PSPM) and in control, Kosaric Medium (KM) in triplicate. The initial cell weight of S. platensis was 6.0 mg/l which attained a maximum weight of 913.13 mg/l on the 10th day of culture in the control KM followed by 699.07, 612.13, 538.99 and 377.48 mg/l that grown in 0.40, 0.30, 0.50 and 0.60 g/l of PSPM respectively. Similar trend was observed in the case of chlorophyll a content ranging 3.57 to 8.15 mg/l. The specific growth rate (SGR, μ/day) of S. platensis on the basis of cell weight and chlorophyll a content was recorded in the ranges of 0.41 to 0.50 and 0.41 to 0.49, respectively, for all the treatments. The SGR on the basis of cell weight and chlorophyll a was recorded significantly (p